Overview of Usual Food Leftovers in Inpatients at the Jailolo Regional General Hospital, West Halmahera Regency: Overview of Usual Food Leftovers in Inpatients at the Jailolo Regional General Hospital, West Halmahera Regency (International Journal of Scientific Research and Management (IJSRM), 2021)
Hospital nutrition services are part of a complete health service. Each hospital provides nutritional services, not only providing food for patients and staff, but the most important thing is the provision of food that meets the needs of human metabolism for recovery during treatment. Food waste is the amount of food that is not eaten or not consumed by the patient. The purpose of this study was to determine the type of food and the amount of leftover food that was not consumed by patients who received regular food at the Jailolo Hospital. The type of research used is descriptive with sampling using purposive sampling as many as 20 respondents. The results showed that of the 20 respondents using the Comstock method, the average patient leftover food left a lot (> 20%) in the staple food type 40%, animal side dishes 35%, vegetable side dishes 30%, vegetables 30% and fruit 40%. Based on the results of the study, it can be concluded that most of the respondents still left a lot of food and it is recommended for nutrition installations to improve the quality and taste of the food served so that there is no more food left.